2017
DOI: 10.5901/mjss.2017.v8n1p123
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction, Efficiency, and Capital Structure as Determinants of Performance Transportation Companies in Indonesia

Abstract: This study aimed to describe the influence of customer satisfaction, efficiency and optimal capital structure to the increase of the performance of transportation companies in Indonesia. The study was designed in the relationship between variables. The data used is secondary data obtained from the Indonesian Capital Market Directory (ICMD) and the website of 22 companies that were used as samples for 3 years. Data were analyzed using descriptive and inferential statistics analysis to test the hypothesis. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…Firm's size has a positive effect on leverage 3.1.2.7 Firm's efficiency. Following few studies in the literature (Margaritis and Psillaki, 2007;Akhtar et al, 2016;Mursalim et al, 2017;Njagi et al, 2017;Ding and Siclkes, 2018), this work further argues that firm efficiency has a significant effect on its leverage. This is because a more efficient firm has a high probability of reporting consistent profit over time.…”
Section: Determinantsmentioning
confidence: 67%
See 2 more Smart Citations
“…Firm's size has a positive effect on leverage 3.1.2.7 Firm's efficiency. Following few studies in the literature (Margaritis and Psillaki, 2007;Akhtar et al, 2016;Mursalim et al, 2017;Njagi et al, 2017;Ding and Siclkes, 2018), this work further argues that firm efficiency has a significant effect on its leverage. This is because a more efficient firm has a high probability of reporting consistent profit over time.…”
Section: Determinantsmentioning
confidence: 67%
“…Yet, the determinant does not enjoy a unanimous consensus among these few studies. While Njagi et al (2017) reports a positive and insignificant effect of efficiency on capital structure, studies (Margaritis and Psillaki, 2007;Akhtar et al, 2016;Mursalim et al, 2017) have reported a positive and significant impact of efficiency on capital structure decisions of firms. Still, Ding and Siclkes (2018) note a significant negative relationship between risk structure and efficiency.…”
Section: Determinantsmentioning
confidence: 98%
See 1 more Smart Citation
“…LRT is not only an answer to counter urban sprawl in a big city like Bandung, but it is also an implementation of technology innovation that holds sustainability value in the economy, society, and environment (Sukarno et al, 2016). By bringing out the sustainable transportation concept as an innovative system, there is a chance of lack of adaption or refusal to the new transportation from the people (Sanusi, Thayf, & Alamzah, 2017;Sharma & Newman, 2017). In order to succeed in the development of a new transportation system, public transportation should be perceived as a consumer-oriented market (Molander, 2018;Sanusi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By bringing out the sustainable transportation concept as an innovative system, there is a chance of lack of adaption or refusal to the new transportation from the people (Sanusi, Thayf, & Alamzah, 2017;Sharma & Newman, 2017). In order to succeed in the development of a new transportation system, public transportation should be perceived as a consumer-oriented market (Molander, 2018;Sanusi et al, 2017). Hence, it is important to examine the market readiness of potential public transportation users.…”
Section: Introductionmentioning
confidence: 99%